Procedure for implementation of strategic environmental assessment in the field of land management on the basis of integration models - Dorosh, О.; Dorosh, А.; Derkulskyi, R.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2021)
This article analyses the legal framework for strategic environmental assessment of state planning documents in the EU, where such an assessment has been conducted for a long time, as well as in Ukraine. The lack of scientific and methodological bases for the implementation of the procedure of strategic environmental assessment in the field of land management has been established. The procedure for implementing the SEA in land management has been updated, namely for land management documentation, that is a subject to such assessment. The stage of development of such documentation on which it is most expedient to carry out SEA is offered.In the framework of this study, land management documentation, that is a subject to strategic environmental assessment, as well as the conditions under which individual documents are subject to SEA are defined. The goals and objectives of the SEA in the field of land management are defined, as well as the main stages of the SEA, in particular in the field of land management.We have analysed the models of integration of strategic environmental assessment into land management and found that the introduction of partial and complete models of integration of SEA into land management is the most appropriate. The list of components which should be contained by the SEA of land management documentation is offered, and also the most expedient analytical tools necessary at realization of SEA are defined.Key words: strategic environmental assessment, SEA, land management documentation, nature reserves.